A Combined Antitumor Strategy Mediated by a New Targeted Nanosystem to Hepatocellular Carcinoma - Farinha D (Dove Medical Press, 2021)
Dina Farinha,1,2 Michael Migawa,3 Ana Sarmento-Ribeiro,1,4,5 Henrique Faneca1,2 1CNC - Center for Neuroscience and Cell Biology (CNC), University of Coimbra, Coimbra, Portugal; 2Institute for Interdisciplinary Research (IIIUC), University of Coimbra, Coimbra, Portugal; 3Ionis Pharmaceuticals Inc, Carlsbad, USA; 4Laboratory of Oncobiology and Hematology (LOH) and University Clinic of Hematology, Faculty of Medicine, University of Coimbra, Coimbra, Portugal; 5Clinical Hematology Department, Centro Hospitalar Universitário de Coimbra (CHUC), Coimbra, PortugalCorrespondence: Henrique FanecaCNC - Center for Neuroscience and Cell Biology (CNC), University of Coimbra, Coimbra, 3004-504, PortugalTel +351-239-820-190Fax +351-239-853-607Email henrique@cnc.uc.ptBackground: Hepatocellular carcinoma (HCC) is one of the main causes of cancer-related death. Sorafenib, which is the first-line therapy for this disease, is associated with reduced therapeutic efficacy that could potentially be overcome by combination with selumetinib. In this context, the main goal of this work was to develop a new nanosystem, composed of a polymeric core coated by a lipid bilayer containing the targeting ligand GalNAc, to specifically and efficiently co-deliver both drugs into HCC cells, in order to significantly increase their therapeutic efficacy.Methods: The physicochemical characterization of hybrid nanosystems (HNP) and their components was performed by dynamic light scattering, zeta potential, matrix-assisted laser desorption ionization – time of flight mass spectroscopy, and transmission electron microscopy. Cellular binding, uptake and specificity of HNP were evaluated through flow cytometry and confocal microscopy. The therapeutic activity was evaluated namely through: cell viability by the Alamar Blue assay; cell death by flow cytometry using FITC-Annexin V; caspases activity by luminescence; mitochondrial membrane potential by flow cytometry; and molecular target levels by Western blot.Results: The obtained data show that these hybrid nanosystems present high stability and loading capacity of both drugs, and suitable physicochemical properties, namely in terms of size and surface charge. Moreover, the generated formulation allows to circumvent drug resistance and presents high specificity, promoting great cell death levels in HCC cells, but not in non-tumor cells. This potentiation of the antitumor effect of co-loaded drugs was carried out by an increased programmed cell death, being associated with a strong reduction in the mitochondrial membrane potential, a significant increase in the activity of caspases 3/7 and caspase 9, and much greater number of annexin V-positive cells.Conclusion: The developed formulation resulted in a high and synergistic antitumor effect, revealing a translational potential to improve therapeutic approaches against HCC.Keywords: hepatocellular carcinoma, hybrid nanosystems, drug delivery, GalNAc, sorafenib, selumetinib